Strategi Pengembangan Inkubator Bisnis Sebagai Lembaga Pendampingan Perusahaan Pemula: Studi Kasus Inkubator Bisnis IPB - Heriyanto S Soba; Rokhani Hasbullah; Nunung Nuryartono (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Business Incubator is a model in growing technology-based entrepreneurship. Compared with the other countries, the business incubator in Indonesia has not been well developed. In fact, the contribution of the business incubator is significant for the successes of the entrepreneurs and the economy in general. This study aimed to analyze the development strategy of business incubators (IncuBie) of IPB by analyzing the internal (Internal Factor Evaluation/IFE) and external (External Factor Evaluation/EFE) factors. This study applied SWOT analysis (Strengths-Weaknesses-Opportunities-Threats), and determined the alternative development strategy using Quantitative Strategic Planning Matrix (QSPM). The SWOT analysis showed four alternative development strategies. Meanwhile, the QSPM matrix analysis showed that an interesting strategy to be selected from various strategic alternatives that are available is by increasing the support to the business incubator through the implementation of regulation and provision of particular financing scheme based on its performance and services to the tenants. This strategy managed a number of strengths to take advantage of the existing opportunities (strengths-opportunities/SO) with the highest total attractive score (STAS).Keywords: business incubator, IFE, EFE, SWOT, QSPM